Analog characteristics of n-type vertically stacked nanowires. (November 2021) - Mariniello, Genaro; Carvalho, Cesar Augusto Belchior de; Cardoso Paz, Bruna; Barraud, Sylvain; Vinet, Maud; Faynot, Olivier; Antonio Pavanello, Marcelo
Highlights: The device is composed of two stacked nanowire levels: omega-gate and a GAA. The measurements were performed at room temperature and with grounded substrate. The weak inversion region presents almost the same behavior with gm/IDS of 38 V-1. The maximum AV was obtained for lower channel width and higher channel length devices. Narrow and longer devices stacked nanowires present better distortion properties. Abstract: This paper presents the fundamental analog figures of merit, such as the transconductance, output conductance, transconductance over drain current ratio, intrinsic voltage gain and harmonic distortion (or non-linearity), of n-type vertically stacked nanowires with variable fin width and channel length. To have a physical insight on the results, the basic electrical parameters such as threshold voltage, subthreshold slope and low field electron mobility of the analyzed transistors were also studied. The studied analog parameters are presented in function of the transconductance over drain current, to allow for the comparison at the same inversion level.